MENINGKATKAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN GRUP INVESTIGASI (GI) SISWA KELAS XI SMK NEGERI 11 MERANGIN - Anggraini, Nice (MAT-EDUKASIA, 2018)
The purpose of this study was to improve students' mathematics learning outcomes using the Group Investigation (GI) learning model of statistical material. The research method used is classroom action research. The research subjects were class XI students of TKJ SMK Negeri 11 Merangin with a total of 23 students, 15 of whom were male and 8 of them were female. The object of the research is the Investigation Group (GI) learning model. The design of this study consisted of planning, implementation, evaluation and observation, and reflection using three cycles. The results of this study obtained an average of mathematics learning outcomes in the first cycle of 62.17, in the second cycle of 69.78 and in the second cycle 70.22. For classical learning completeness in the first cycle, that is 43.48%, the second cycle is 65.22% and in the third cycle is 78.26%. For teacher activities on silkus I, which is 69.22%, on silkus II is 100% and in cycle III is 100%. And for student activities on silkus I is 51.44%, in silkus II is 65.20% and in cycle III is 82.96%. It can be concluded that by implementing the Group Investigation learning model in the learning process it is proven that it can improve the mathematics learning outcomes of students of SMK Negeri 11 Merangin in the 2015/2016 Academic Year both in completing learning and learning activities.